If x3 –3x2 + 3x – 7 =(x +1) (ax? + ...
Question
Fullscreen

If x3 –3x2 + 3x – 7 =(x +1) (ax? + bx +c), then a+b+c= (a) 4 (b) 12 (c) - 10 (d) 3

11th - 12th Class
Maths
Solution
225
Rating
4.0 (1 ratings)
Fullscreen
( x^{3}-3 x^{2}+3 x-7 ) ( =a x^{3}+b x^{2}+c x ) ( +a x^{2}+b x-varepsilon< ) Compare ( , a=1, b=-4 ) Corection Inseed of ( +^{prime}, quad= ) sign ( 0.5 c=7 ) o ( 0 a+b+C=4 )
Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free